Population Pharmacokinetic Meta-Analysis of Denosumab in Healthy Subjects and Postmenopausal Women with Osteopenia or Osteoporosis - Sutjandra, Liviawati; Rodriguez, Rachelle D.; Doshi, Sameer; Ma, Mark; Peterson, Mark C.; Jang, Graham R.; Chow, Andrew T.; Pérez-Ruixo, Juan José (Clinical pharmacokinetics, 2011)
Background and Objective: Inhibition of the receptor activator of nuclear factor k-B ligand (RANKL) is a therapeutic target for treatment of bone disorders associated with increased bone resorption, such as osteoporosis. The objective of this analysis was to characterize the population pharmacokinetics of denosumab (AMG 162; Prolia®), a fully human IgG2 monoclonal antibody that binds to RANKL, in healthy subjects and postmenopausal women with osteopenia or osteoporosis. Methods: A total of 22944 serum free denosumab concentrations from 495 healthy subjects and 1069 post-menopausal women with osteopenia or osteoporosis were pooled. Denosumab was administered as either a single intravenous dose (n = 36), a single subcutaneous dose (n = 469) or multiple subcutaneous doses (n= 1059), ranging from 0.01 to 3 mg/kg (or 6–210 mg as fixed mass dosages), every 3 or 6 months for up to 48 months. An open, two-compartment pharmacokinetic model with a quasi-steady-state approximation of the target-mediated drug disposition model was used to describe denosumab pharmacokinetics, using NONMEM Version 7.1.0 software. Subcutaneous absorption was characterized by the first-order absorption rate constant (k a ), with constant absolute bioavailability over the range of doses that were evaluated. Clearance and volume of distribution parameters were scaled by body weight, using a power model. Model evaluation was performed through visual predictive checks. Results: The subcutaneous bioavailability of denosumab was 64%, and the k a was 0.00883 h −1 . The central volume of distribution and linear clearance were 2.49 L/66 kg and 3.06 mL/h/66 kg, respectively. The baseline RANKL level, quasi-steady-state constant and RANKL degradation rate were 614ng/mL, 138 ng/mL and 0.00148 h −1 , respectively. Between-subject variability in model parameters was moderate. A fixed dose of 60 mg provided RANKL inhibition similar to that achieved by equivalent body weight-based dosing. The effects of age and race on the area under the serum concentration-time curve of denosumab were less than 15% over the range of covariate values that were evaluated. Conclusions: The non-linearity in denosumab pharmacokinetics is probably due to RANKL binding, and denosumab dose adjustment based on the patient demographics is not warranted.